Prediction of soil engineering properties using electrical resistivity values at controlled moisture content- A conceptual paper - Qazi, W.H. (Asian Research Publishing Network, 2016)
Geo-electrical assessment is an appealing instrument for depicting subsurface properties without soil unsettling influence and also can be considered as an intermediary for the spatial and fleeting variability of numerous other soil physical properties (i.e. structure, water substance, or liquid synthesis, porosity, degree of saturation etc.) and strength parameters (i.e. cohesion and angle of friction). Since the system is non-dangerous and exceptionally delicate, it offers an extremely fascinating apparatus for depicting the subsurface properties without burrowing. In this paper a conceptual model is developed for the assessment of slope stability and FOS using electrical resistivity values of the insitu soil at controlled moisture content (30). The obtained results will be interrelated with soil physical properties (moisture content, plasticity index, specific gravity, porosity, degree of saturation etc.), chemical properties (Cation exchange capacity (CEC), pH and mineralogy) and strength parametres of soil such as, cohesion and internal angle of friction. Assessment of geotechnical hazards will incorporate by applying 1D electrical resistivity survey on a laboratory scale using fabricated soil box. The established results will hopefully contribute in the calculations of bearing capacity, slope stability and factor of safety for soil. Â© 2006-2016 Asian Research Publishing Network (ARPN).